2008
DOI: 10.1142/s0218271808012644
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Ground Test of Inertial Sensor for Astrod I

Abstract: An electrostatically controlled torsion pendulum has been constructed to investigate the performance of the ASTROD I inertial sensor on the ground. The twist motion of the pendulum is monitored by a capacitive transducer and controlled by an electrostatic actuator. The preliminary experimental results show that the torque resolution of the pendulum is 2×10 −12 N m Hz −1/2 at 3 mHz. Further improvements under consideration for the inertial sensor are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…A torsion pendulum study for a prototype inertial sensor for ASTROD I is reported in Ref. 63. In this prototype torsion pendulum, the twist motion of the test mass is monitored and servo-controlled.…”
Section: Astrod Imentioning
confidence: 99%
“…A torsion pendulum study for a prototype inertial sensor for ASTROD I is reported in Ref. 63. In this prototype torsion pendulum, the twist motion of the test mass is monitored and servo-controlled.…”
Section: Astrod Imentioning
confidence: 99%
“…The initial relative position between the TM and the EH is accurately adjusted by the hexapod when the box is suspended. The TM is controlled motionless with respect to the EH by exerting electrostatic forces via electrodes around the TM here [22,23]. Due to the electrostatic control scheme, the components of the torsion pendulum have very small oscillation amplitude, and then the local background gravity gradient can be neglected [11].…”
Section: Pendulums and Experimental Setupmentioning
confidence: 99%
“…The feedback voltages associated with the calibrated sensitivity coefficients indicate the variations of residual forces and torques acting on the PM. The operational principle is introduced in detail in [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%